Permeability Evolution in Sandstone and Carbonate after Fracture Induced by CO2 Injection - Olu-Ojo, Toluwalope (Curtin University, 2020)
Effective carbon dioxide sequestration is hinged on rock permeability, a dynamic property dependent on the thermo-physical conditions of the storage rock. Changes to rock permeability in Berea sandstone and Savonnières limestone rocks undergoing triaxial compression, up to failure, are observed and analysed using live brine and supercritical carbon dioxide as injection fluids. Results obtained indicate the effect of induced fracture(s) on permeability evolution in the rocks as geomechanical or geochemical reactions occur in the samples.